2004
DOI: 10.1068/p5207
|View full text |Cite
|
Sign up to set email alerts
|

The Tale is in the Tail: An Alternative Hypothesis for Psychophysical Performance Variability in Dyslexia

Abstract: Dyslexic groups have been reported to display poorer mean performance than groups of normal readers on a variety of psychophysical tasks. However, inspection of the distribution of individual scores for each group typically reveals that the majority of dyslexic observers actually perform within the normal range. Differences between group means often reflect the influence of a small number of dyslexic individuals who perform very poorly. While such findings are typically interpreted as evidence for specific per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 44 publications
6
57
0
Order By: Relevance
“…Simulations of performance on adaptive discrimination tasks and categorical tasks that included errant trials yield patterns of group results that concur with those seen in studies of perceptual abilities in individuals with dyslexia (Roach et al, 2004;Davis, Castles, McAnally & Gray, 2001) although Breier et al (2001) found a deficit in phoneme categorization in a group of dyslexic children whether or not they were diagnosed with ADHD. Roach et al (2004) argue that in order to distinguish poor performance that is due to nonsensory factors from poor performance linked to a specific perceptual deficit, it is necessary to determine whether a task has construct validity, i.e. that it is tapping the dimension that is being investigated.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…Simulations of performance on adaptive discrimination tasks and categorical tasks that included errant trials yield patterns of group results that concur with those seen in studies of perceptual abilities in individuals with dyslexia (Roach et al, 2004;Davis, Castles, McAnally & Gray, 2001) although Breier et al (2001) found a deficit in phoneme categorization in a group of dyslexic children whether or not they were diagnosed with ADHD. Roach et al (2004) argue that in order to distinguish poor performance that is due to nonsensory factors from poor performance linked to a specific perceptual deficit, it is necessary to determine whether a task has construct validity, i.e. that it is tapping the dimension that is being investigated.…”
Section: Introductionsupporting
confidence: 54%
“…It is therefore important to examine the performance of individual participants in both the DYS and AR groups to get a better sense of the proportion of individuals showing poor performance on speech perception tasks, even when group effects are not significant. A further rationale for this kind of analysis is to ascertain whether any participants are consistently poor at subtasks that are assessing a given processing ability, or whether poor performance appears to be more random, and therefore more likely to be due to reasons other than a perceptual deficit (Roach et al, 2004;Heath et al, 2006). Also, if poor categorization ability is likely to result in further perceptual difficulties when the speech signal is degraded, we expect to see that individuals showing poor performance on categorization tasks also show higher thresholds in the words in noise tasks.…”
Section: Individual Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The repetition task is particularly vulnerable to this type of criticism as it involves several cognitive components. Most psychoacoustic tasks are also laden with task demands other than sensory registration [101][102][103] (see Ramus & Ahissar [40] for a similar argument). For example, the requirement for explicit judgements introduces potential interference from auditory memory or even verbal processes that may be recruited to label the stimuli.…”
Section: Theoretical and Methodsological Issues (A) On Tasks And Measuresmentioning
confidence: 99%
“…This is important since deficits in attention have the potential to affect performance on sensory tests (Peli and Marcia-Perez 1997;Stuart et al 2001;Davis et al 2001;Roach et al 2004). This, therefore, raises the question of if, or to what extent, the observed sensory deficits might reflect underlying attentional problems 1, 2 .…”
Section: Introductionmentioning
confidence: 99%